PARTISIPASI MASYARAKAT PADA PEMBANGUNAN INFRASTRUKTUR JALAN PERTANIAN MELALUI (PNPM-PPIP) DI DESA KINI KECAMATAN HILIPUK KABUPATEN YAHUKIMO - Yakobus ., Bahabol; Caroline B. D. Pakasi; Jean F. J. Timban (Sam Ratulangi University, 2018)
This study aims to what extent the community involvement in the development of agricultural road infrastructure through the PNPM-PPIP program. This study lasted for 3 months from September until November 2017. The research location is in Kini Village, Hilipuk Sub-District, Yahukimo Regency. The type of data were collected in this research is primary data and secondary data. Selection of the sample used purposive sampling method. The number of respondents is 20 people who are Community Leaders in the implementation of Local Community Organization (CSO) activities. The analysis technique used in this research is qualitative descriptive. The results showed that community participation in the development of agricultural road infrastructure in Kini Village is in the medium category. Because of the three stages of infrastructure development, only the maintenance phase is the stage that involves the most participation of the community while the planning stage and the implementation stage there is no participation from the community. Community involvement in the maintenance phase because at this stage the community has felt the result of the development of agricultural road access infrastructure.